High aspect ratio germanium nanowires obtained by dry etching. Issue 13 (2016) - Guilloy, Kevin; Pauc, Nicolas; Gassenq, Alban; Calvo, Vincent
ABSTRACT: We present here a reactive ion etching recipe to fabricate germanium nanowires. We used a combination of Cl2, N2 and O2 and studied the influence of both the gas pressure and the O2 mass flow on the morphology of the nanowires. 5 µm long nanowires with an aspect ratio of 20 are demonstrated with smooth surfaces and a tapering below 20 nm/µm. We also show that both gold and aluminum can be used as hard mask; the latter achieving a selectivity with germanium above 100.